STUDYING OF THE LICHENS DIVERSITY IN THE CHULAK RIDGE (Experimental biology, 2024)
There is practically no information about the lichens of the Chulak ridge, despite the fact that they have a significant biomass and are one of the essential components of most plant communities. Therefore, the purpose of our work was to study the diversity of lichens on the territory of the Chulak ridge and analyze data on their distribution. The scientific and practical significance of the work lies in obtaining data on the diversity of lichens, which serve as indicators of soil types, rocks and other natural phenomena that are useful to humans. The material for the article was the authors' own collections conducted in 2022-2023 and stored in the herbarium of the Institute of Botany and Phytointroduction. The preparation of lichen preparations, their study and identification were carried out according to the standard methodology. The samples were studied using a Levenhuk MED D45T LSD light microscope. A list of lichen species is provided, indicating the substrate and the coordinates of the collection. 22 species of lichens belonging to three classes have been found on the territory of the Chulak ridge. The class Candelariomycetes is represented by one order, one family of the same name, and two species. The class Eurotiomycetes is also not numerous: only two species from the order Verrucariales and the family Verrucariaceae. The largest class of Lecanoromycetes is represented by 7 orders, 8 families, 14 genera and 18 species. Most of the identified species (14 species, 63.6% of the total number of species) are confined to stones and outcrops of basic rocks. Only 1 species (4.5%) was found on mosses. Three species (13.6%) were observed on the bark of twigs of Atraphaxis sp. and branches of Cerasus tianshanica. Five species (22.7%) are found on the soil, and two can exist as free-living, and Scytinium palmatum can also live on stones. The species Xanthoria elegans and Protoparmeliopsis muralis are most often noted in the research area. Two species Scytinium palmatum and Anaptychia roemeri were found for the first time in Kazakhstan. The value and practical significance of the conducted research lies in obtaining data on the species composition of lichens, their distribution and their association with different types of substrates.
Keywords: Desert lowlands; lichen biota; lichen manna; substrate association of lichens